2018
DOI: 10.1002/pc.25065
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Glass Fiber‐Reinforced Polyester Composites: Comparing Toughening Effects of Modified Graphene Oxide and Core‐Shell Rubber

Abstract: The role of nanoparticles in the fracture toughness of glass fiber‐reinforced polyester composites (GFRPs) was investigated. An unsaturated polyester resin (UPR) and a vinyl ester resin (VER) were toughened by two distinct methods: (1) incorporating a very low loading (0.04 wt%) of alkyl or vinyl modified graphene oxide (mGO); or (2) adding core‐shell rubber (CSR, 1 and 5 wt%). For unreinforced resins, results from compact tension tests revealed that adding 0.04 wt% of mGO increased the fracture toughness (GIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…The fillers are uniformly dispersed in the matrix, which could be the reason for improved tensile, tear and hardness. [ 24 ] Figure 4D shows the EDAX spectrum of NR 4 composite designation indicating the peaks of Co and C with average counts (peak length). Thus, the process of two‐roll mil effectively disperses the reinforcements throughout the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The fillers are uniformly dispersed in the matrix, which could be the reason for improved tensile, tear and hardness. [ 24 ] Figure 4D shows the EDAX spectrum of NR 4 composite designation indicating the peaks of Co and C with average counts (peak length). Thus, the process of two‐roll mil effectively disperses the reinforcements throughout the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Matadi Boumbimba et al [18] observed that the triblock copolymer additive increased the impact resistance of the glass fiber/epoxy composite structure. Some other additives used to improve the mechanical properties of epoxy resin are graphene, [23] carbon nanotube, [24] core-shell rubber, [25] silica, [26] clay, [27] alumina, [28] titania, [29] zirconia, [30] and boron carbide (B 4 C). [31][32][33] Boron carbide has been used in a wide range of fields such as military, nuclear reactors, grinding, and cutting tools due to its high hardness, neutron capture, and thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…They observed 46%, 54%, and 66% increase in the tensile, flexural and compressive moduli, respectively with the addition of 0.5 wt% grafted GO. Liu et al 13 introduced vinyl modified GO (mGO) into GFRCs and reported 49% increase in fracture toughness with the addition of 0.04 wt% mGO.…”
Section: Introductionmentioning
confidence: 99%